(untitled) (Journal of history, 2020)
This article studies role of Central Asia in China’s foreign strategy. Chi- nese policy towards Central Asia is based on Concept of «turning neighbors into partners» adopted in early 2000’s at XVI Congress of CCP. In 2003 this concept was modified by thesis of «peaceful, secure and rich neighbor- hood». China’s foreign policy towards Central Asia has changed due to cur- rent situation and geopolitical environment and has gone through several periods. In order to understand China’s foreign policy strategy in Central Asia it is necessary to understand Chinese interests in the region. Despite fears of «Chinese expansion» widespread among population and political elites of Central Asian countries China is considered as an alternative to Russia and the West in issues of regional security and economic coopera- tion. All of this proves the necessity of taking into consideration the factor of China in Central Asia. We need to face the reality.